2015
DOI: 10.1007/s11255-015-0920-5
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in patients diagnosed with benign prostatic hyperplasia

Abstract: BackgroundSymptoms of depression are common in patients diagnosed with benign prostatic hyperplasia (BPH) and are usually a reaction to deterioration of health, severity of lower urinary tract symptoms, and erectile dysfunction. The aim of this observational study was to evaluate the prevalence of depressive symptoms in patients diagnosed with BPH and factors affecting their occurrence in a large Polish cohort.Patients and methodsFour thousand thirty-five men (4,035) diagnosed with BPH participated in the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 44 publications
2
44
1
3
Order By: Relevance
“…On that scale that ranged from 0 to 21 (higher being worse), benign prostate hypertrophy was associated with higher depression, which is in accordance with a recent study that found a higher than normal prevalence of depression among this group of patients . However, in contrary to expectations, dysthyroidism was also associated with higher depression.…”
Section: Discussionsupporting
confidence: 90%
“…On that scale that ranged from 0 to 21 (higher being worse), benign prostate hypertrophy was associated with higher depression, which is in accordance with a recent study that found a higher than normal prevalence of depression among this group of patients . However, in contrary to expectations, dysthyroidism was also associated with higher depression.…”
Section: Discussionsupporting
confidence: 90%
“…However, after adjustment for the presence of BPH, the risk of depression was not significantly different for men with treated BPH compared with unexposed men. Results of a cross‐sectional study of 4035 men with BPH in Poland indicated that current use of 5‐ARIs was associated with a 1.52‐fold higher prevalence of depression symptoms; however, the results of this study also suggest that increased severity of BPH symptoms and longer duration of BPH treatment were associated with a higher prevalence of depression symptoms . The results of these prior studies, in which the increased risks of depression diminished and were no longer significant after adjusting for BPH, suggest that confounding by indication may explain the observed increased risk of depression in users of 5‐ARIs.…”
Section: Discussionmentioning
confidence: 51%
“…Results of another study of 16,130 men diagnosed with BPH reported that the risk of depressive disorder was 1.87 times higher (95% confidence interval [CI] 1.63–2.16) than the risk of depression in a matched cohort of 48,390 men without BPH . With respect to BPH treatment, two studies evaluating men with BPH reported increased risks of depression in men with BPH treated with 5‐ARIs compared with men without BPH . However, because the comparators in these studies were men without BPH, it is possible that the observed increased risks of depression may have been confounded by the underlying disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the concept, depression and decreased HRQoL is also found in those having treatments related to BPH. 84 Patients before undergoing TURP experiences more depressed, worried and another psychiatric morbidity due to by the unsolved prostatic symptoms and pain affecting their marital status and HRQoL, unsuccessful medical treatment, urinary dysfunction, and prostate cancer. 83 Moreover, worsening functional impairments and physical symptoms concerned with BPH trigger depression and anxiety.…”
Section: Emotional and Psychological Factorsmentioning
confidence: 99%